Immunological Evaluation and Comparison of Different EV71 Vaccine Candidates - Ai-Hsiang Chou; Chia-Chyi Liu; Jui-Yuan Chang; Shu-Pei Lien; Meng-Shin Guo; Hau-Pong Tasi; Kuang-Nan Hsiao; Shih-Jen Liu; Charles Sia; Suh-Chin Wu; Min-Shi Lee; Chia-Hsin Hsiao; et al. (Clinical and Developmental Immunology)
Enterovirus 71 (EV71) and coxsackievirus A16 (CVA16) are major causative agents of hand, foot, and mouth diseases (HFMDs), and EV71 is now recognized as an emerging neurotropic virus in Asia. Effective medications and/or prophylactic vaccines against HFMD are not available. The current results from mouse immunogenicity studies using in-house standardized RD cell virus neutralization assays indicate that (1) VP1 peptide (residues 211–225) formulated with Freund’s adjuvant (CFA/IFA) elicited low virus neutralizing antibody response (1/32 titer); (2) recombinant virus-like particles produced from baculovirus formulated with CFA/IFA could elicit good virus neutralization titer (1/160); (3) individual recombinant EV71 antigens (VP1, VP2, and VP3) formulated with CFA/IFA, only VP1 elicited antibody response with 1/128 virus neutralization titer; and (4) the formalin-inactivated EV71 formulated in alum elicited antibodies that cross-neutralized different EV71 genotypes (1/640), but failed to neutralize CVA16. In contrast, rabbits antisera could cross-neutralize strongly against different genotypes of EV71 but weakly against CVA16, with average titers 1/6400 and 1/32, respectively. The VP1 amino acid sequence dissimilarity between CVA16 and EV71 could partially explain why mouse antibodies failed to cross-neutralize CVA16. Therefore, the best formulation for producing cost-effective HFMD vaccine is a combination of formalin-inactivated EV71 and CAV16 virions.